On South Sudan, in English. Review of the Books by Peter Martell “First Raise A Flag: How South Sudan Won the Longest War but Lost the Peace” and John Young “South Sudan’s Civil War: Violence, Insurgency and Failed Peacemaking” (Review) - SHAROVA Anna Yurevna (Ученые записки Института Африки Российской академии наук)
Anna Sharova reviews two recent books separately published by two English language authors – P. Martell and J. Young. The books are very different in style and mood. While P. Martell presents an excellent example of British journalist prose in the style of his elder compatriots Somerset Maugham and Graham Greene, who did their reporting and writing from exotic countries during fateful periods of history, J. Young offers a more academic, though no less ‘on the spot’ analysis of the situation in the youngest independent country of Africa.